ChemInform Abstract: Synthesis of Active Tin: An Efficient Reagent for Allylation Reaction of Carbonyl Compounds. Issue 29 (July 2015) - Sinha, Arun Kumar; Sil, Amit; Sasmal, Anup Kumar; Pradhan, Mukul; Pal, Tarasankar
Abstract Homoallylic alcohols (III), (V) are obtained by allylation of the various substituted aldehydes or ketones using high purity Sn(0) as catalyst.